Documentary video on DJ playing techniques in the analog and digital era - Farah Fauziah; Kelso Lineus; Bonifacia Bulan Aruming Tyas (Asosiasi Program Studi Desain Komunikasi Visual Indonesia (Asprodi DKV), 2025)
This documentary explores the evolving techniques of Disc Jockeys (DJs) from the analog to the digital era. It addresses the shift from the intricate art of vinyl manipulation in the 1990s to the more accessible, technology-driven methods of today, such as auto-sync features on digital DJ software. The production involved comprehensive pre-production, including research, story development, and scriptwriting, followed by a multi-day production phase for A-roll, B-roll, and audio recording. Post-production focused on editing and creating supporting media. The resulting documentary effectively illustrates the differences in DJing techniques across eras, receiving positive feedback for its engaging visual and audio elements, clear messaging, and success in delivering new knowledge to its audience.